2017
DOI: 10.1002/hbm.23815
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity‐based parcellation of the anterior limb of the internal capsule

Abstract: The anterior limb of internal capsule (ALIC) is an important locus of frontal-subcortical fiber tracts involved in cognitive and limbic feedback loops. However, the structural organization of its component fiber tracts remains unclear. Therefore, although the ALIC is a promising target for various neurosurgical procedures for psychiatric disorders, more precise understanding of its organization is required to optimize target localization. Using diffusion tensor imaging (DTI) collected on healthy subjects by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 73 publications
0
32
0
8
Order By: Relevance
“…Building on psychosurgical lesioning experience [2], DBS is often targeted at ventral capsule/ventral striatum (VC/VS) areas [3], and normalizes pathological hyperconnectivity to the prefrontal cortex (PFC) [4]. At our institute, DBS is applied within the ventral part of the anterior limb of the internal capsule (vALIC) [5], a region which is known for large inter-subject white matter (WM) tracts variability [6,7]. We hypothesized that treatment response could depend on the location of the active contacts with respect to these tracts, which is currently not accounted for in DBS target planning based on anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Building on psychosurgical lesioning experience [2], DBS is often targeted at ventral capsule/ventral striatum (VC/VS) areas [3], and normalizes pathological hyperconnectivity to the prefrontal cortex (PFC) [4]. At our institute, DBS is applied within the ventral part of the anterior limb of the internal capsule (vALIC) [5], a region which is known for large inter-subject white matter (WM) tracts variability [6,7]. We hypothesized that treatment response could depend on the location of the active contacts with respect to these tracts, which is currently not accounted for in DBS target planning based on anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the contralateral pathway is more important than the ipsilateral pathway in the processing of auditory stimulation (Khosla et al, 2003;Langers et al, 2005), of which 70-80% from the contralateral side and 20-30% comes from the ipsilateral side. Furthermore, the anterior limb of the internal capsule is believed to be involved in cognitive function, such as decision-making, attention, memory and so on (Nanda et al, 2017). For example, the change of QA value in this area may be related to the psychological problems such as anxiety and depression which often occur in patients with sudden hearing loss (Arslan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The white matter anatomy of the ALIC has been shown to be well-ordered, but variable along individuals. [11,[14][15][16] It was hypothesized that stimulation of disrupted dopaminergic connections from the ventral tegmental area (VTA) to the nucleus accumbens/striatum might be related to treatment response for TRD. [17] Research based on this hypothesis disentangled two important fiber pathways coursing through the ALIC: the anterior thalamic radiation (ATR), and the superolateral medial forebrain bundle (slMFB) [11].…”
Section: Introductionmentioning
confidence: 99%